SHELLS STRESS ANALYSIS USING A VARIATIONAL METHOD BASED ON THREE-DIMENSIONAL FUNCTIONS WITH FINITE CARRIERS - Abdulaziz Abrahem, Hussain; Kamil Sebur, Ali; Obeid Hassoun, Enaam; Khairullin, F.S.; Sakhbiev, O.M. (Journal of Applied Engineering Science, 2020)
A modification of the method is presented, which allows one to analysis a thin shells calculation by specifying the geometry only in the Cartesian coordinate system. A variational method is presented for determining the stress-strain state of three-dimensional elastic structures based on the use of approximating functions with finite carriers of an arbitrary degree of approximation. The presented method can be successfully used both for the calculation of three-dimensional composite structures and for the calculation of thin shells using curvilinear coordinate systems, a comparison between modeling of equations programming with Ansys software gives a good indication for corrections of the method modification.